Feeding the transcendent body - Yúdice, George (Tropelías: Review of Literary Theory and Comparative Literature, 2018)
"A language which repeats no other speech, no other Promise, but postpones death indefinetely by ceaselessly opening a space where it is always the analogue of itself". This is Foucault’s account of an aesthetics of transcendence, where transcendence is defined as the experience of infinìty (call ìt mysticism, the sublime, or poststructuralìst écriture) withìn a medium that feeds on itself. This essay examines eating and the self-consuming body as the most basic metaphors of the aesthetic process that Foucault describes and asks whether they have not lost their relevance for transcendence in a world of simulation, that is, a world in which everything, even the body, has undergone the banalization (Baudrillard’s term) that results when medium collapses unto itself. It also proposes new and more politically viable metaphors of construing the consumption metaphor.